THIS LETTER IS TO INFORM YOU OF SOME OF THE DISCUSSIONS AT THE SYMPOSIUM SPONSORED BY THE CONSUMER FEDERATION OF AMERICA TITLED, ""INDOOR AIR QUALITY: PROBLEMS AND SOLUTIONS."". [IAQ CONFERENCE] (Tufts Archival Research Center, 2007)
Letter to Kay Thomas from Simon Turner summarizing discussions from the Consumer Federation of America's indoor air quality (IAQ) conference. Focuses on a building systems versus a pollutant-by-pollutant approach to air quality mitigation. Summarizes various other speakers and debates on IAQ issues, highlighting their relationship to the industry.